Assessment of harmonic penetration with embedded PV in Nigerian power system - Amoo, A. L. (Institute of Electrical and Electronics Engineers Inc., 2016)
Assessment of the depth of harmonic power penetration in the Nigerian power system with embedded PV is presented. The paper focuses on the investigation of harmonic voltage and current distortions that could be initiated in the Nigerian power system with distributed PV embedded generations. The harmonic power flow and frequency scan were executed on the network at buses of interest. A twenty-four (24) bus of the existing Nigerian grid has been interconnected with five radial feeders each separately terminated with PV generation. The impedance scan results revealed the level of vulnerability of the network to harmonic distortions with volt and current THDs obtained as 12.98% and 58.5% respectively. Finally, a 200kW embedded PV Grid connected system was implemented in MATLAB/SimPower environment to study the impact of the series reactor harmonic mitigating technique on available power transferred from the PV and was found to reduce by 5%.